2017
DOI: 10.2196/resprot.7904
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management Framework for Emerging Infectious Diseases Preparedness and Response: Design and Development of Public Health Document Ontology

Abstract: BackgroundThere are increasing concerns about our preparedness and timely coordinated response across the globe to cope with emerging infectious diseases (EIDs). This poses practical challenges that require exploiting novel knowledge management approaches effectively.ObjectiveThis work aims to develop an ontology-driven knowledge management framework that addresses the existing challenges in sharing and reusing public health knowledge.MethodsWe propose a systems engineering-inspired ontology-driven knowledge m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…From the metamodel level representations (Pivot metamodel, Alignment rules, Ontology terminology) the objective is to define a full process for knowledge extraction that can be specified for any source of data and any ontology. This way, the Pivot metamodel is specified into a Data model, 3 Alignment rules are specified into a Model transformation and the Target ontology is then populated from the Data model thanks to the Alignment rules and the tools used to specify alignment rules into a model transformation. Once the Target ontology has been populated with its instances, the knowledge base is created.…”
Section: Presentation Of the Framework Conceptsmentioning
confidence: 99%
“…From the metamodel level representations (Pivot metamodel, Alignment rules, Ontology terminology) the objective is to define a full process for knowledge extraction that can be specified for any source of data and any ontology. This way, the Pivot metamodel is specified into a Data model, 3 Alignment rules are specified into a Model transformation and the Target ontology is then populated from the Data model thanks to the Alignment rules and the tools used to specify alignment rules into a model transformation. Once the Target ontology has been populated with its instances, the knowledge base is created.…”
Section: Presentation Of the Framework Conceptsmentioning
confidence: 99%
“…Recent infectious disease outbreaks, including Ebola and the COVID-19 pandemic, have highlighted the critical need for these stakeholders to harness and share knowledge effectively to make informed and timely decisions. [2][3][4] Knowledge management (KM) is a discipline that integrates people, processes, and technology to collect and curate knowledge systematically and connect people to it so they can act effectively. [5][6][7] It can help health care professionals access, share, and apply timely and relevant information.…”
Section: Introductionmentioning
confidence: 99%
“…KM can also facilitate collaboration across professional, organizational, and geographic boundaries, expediting the global health field's responsiveness to emergencies and health and development challenges. 3,8 Within global health, voluntary family planning and reproductive health (FP/RH) programs have made substantial investments to translate research into practice to improve FP/RH services. For example, the United States Agency for International Development (USAID) has collaborated with the Johns Hopkins Center for Communication Programs (CCP) over several decades to share FP/RH and related global health knowledge around the world, through such seminal KM tools and guidelines as the Family Planning High Impact Practices, Family Planning: A Global Handbook for Providers, and more.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general survey of the scenario suggests the need for more effective knowledge management system and transparency of information from the epicenter of viral outbreaks and all pertinent matters concerning the global health emergencies. While reviewing relevance of dissemination of credible information Zhang et al (2017) have expressed concerns about preparedness and timely coordination of response mechanisms globally to cope with the emerging infectious diseases. The authors have suggested the need for generating innovative knowledge management approaches.…”
Section: Introductionmentioning
confidence: 99%